The primary school administrators’ contributions to the organizational socialization of the educational staff and two example cases - Sadık KARTAL (İnönü Üniversitesi Eğitim Fakültesi Dergisi)
The aim of this study is to determine to which degree school administrators discharge their duties concerning the organizational socialization of teachers and the other staff at schools. The research has been made at a primary school in Ankara. A teacher who has been recently appointed to that school and an official has participated in the research. The method of “example case” has been used in the study. In this method, the technique of oral interview – especially individual interview - has been utilized to gather data. Analyzing the example case based on the data gathered through interview has been made according to the criteria defined in Buchanan’s (1974) three stage “first occupation model” which is a model in organizational socialization approaches. The stage of “the first year in the organizational socialization of the employee (basic training and adjustment) in this model has been examined and the following in this stage (1) forming the role part hiatus of the new employee, (2) establishing commitment between the new employee and his colleagues, (3) achieving harmony between the employee and the other parts/units of the organization; and conducting behaviors in order to settle the possible conflicts (4) the realization level of the expectations (experiencing a reality shock if expectations do not come true) (5) the opportunities that the new job provides for the employees, have been taken as basic points in analyzing and interpreting the example case. According to the obtained findings from the research, it has been understood that the administrator doesn’t provide sufficient support for the harmony between the teacher and the official; and at the end of the first year the organizational socialization of these two mentioned people has been supplied thanks to their own individual efforts.